THE SYSTEM OF PROCESSES AND PROJECTS OF THE AIRCRAFT AIRWORTHINESS MAINTENANCE - A. A. Itskovich; G. D. Fainburg; I. A. Fainburg; A. O. Chernov (Научный вестник МГТУ ГА)
The concept of the aviation enterprise as a unified system of processes and projects of the aircraft airworthiness maintenance (AAM) is presented. The relevance of project management tools usage, including the transport branch, is noted; the examples of successful implementation of the development projects at domestic enterprises manufacturing aircraft engines are given. A scheme for the classification of the AAM projects and processes, reflecting their interrelationship, is proposed. The operational activity of the enterprise is a combination of its business processes. The company selects plans and implements the relevant projects for the business processes optimization. At the same time, the projects themselves are the objects of management based on standardized processes. The processes of project management and the main processes of the enterprise are also interrelated and can be objects included in the unified regulations of its units. Increasing the efficiency of operational processes and processes of the aviation enterprise management is the goal of development projects, which are divided into investment projects and organizational changes projects.Limitation of organizational and financial resources of the company requires the identification and systematization of all projects and processes, while the application of project management standards allows to analyze the opportunities and to determine the sequence of their implementation. The importance of accumulating experience of completed projects is shown; the results can become typical methods for planning, organizing the implementation and monitoring of AAM projects. Specific forms of the project management standards implementation for AN-124-100 constructive modification project in LLC Volga-Dnepr Airlines are demonstrated: the control events plan and the project team formation.